(3Ohd GdGSdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3GHQGgje Hf eMeO Hf eSGaQ GdTgjQ HGHf GdUGQe s)
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdcHjQ s
(3GfXQ Qbe (B" 662" (3JGQjNs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
Keywords: (3GdJGQjNs